Disease presentation of 1312 childhood-onset systemic lupus erythematosus: influence of ethnicity - Fiorot, Fernanda J.; Islabão, Aline G.; Pereira, Rosa M.; Terreri, Maria T.; Saad-Magalhães, Claudia [UNESP]; Novak, Glaucia V.; Molinari, Beatriz C.; Sakamoto, Ana P.; Aikawa, Nadia E.; Campos, Lucia M.; Peracchi, Octavio A.; Appenzeller, Simone; et al. (Springer Nature, 2019)
Objective: To evaluate the influence of ethnicity in presentation of childhood-onset systemic lupus erythematosus (cSLE) patients. Methods: This multicenter study included cSLE patients (American College of Rheumatology criteria) followed in 27 Pediatric Rheumatology services of Brazil. Ethnicities were classified in four groups according to the parents’ and all four grandparents’ self-reported ethnicity. The statistical analysis was performed using the Bonferroni’s correction (p < 0.0027). Results: According to ethnic groups, 1537 cSLE patients were classified in Caucasian (n = 786), African-Latin American (n = 526), Asian (n = 8), and others/unknown (n = 217). Comparisons between 1312 African-Latin American and Caucasian revealed similar median age at cSLE diagnosis [12.2(2.6–18) vs. 12.1(0.3–18) years, p = 0.234], time interval to diagnosis [0.25(0–12) vs. 0.3(0–10) years, p = 0.034], and SLEDAI-2K score [14(0–55) vs. 14(0–63), p = 0.781] in both groups. The mean number of diagnostic criteria according to SLICC (6.47 ± 1.911 vs. 5.81 ± 1.631, p < 0.0001) and frequencies of maculopapular lupus rash (8% vs. 3%, p < 0.0001), palate oral ulcers (17% vs. 11%, p = 0.001), tongue oral ulcers (4% vs. 1%, p = 0.001), and nonscarring alopecia (29% vs. 16%, p < 0.0001) were significantly higher in African-Latin American, whereas malar rash (45% vs. 58%, p < 0.0001) was more frequent in Caucasian. The presence of anti-phospholipid antibody (23% vs. 12%, p < 0.0001), low complement levels (58% vs. 41%, p < 0.0001), and isolated direct Coombs test (10% vs. 5%, p = 0.001) was also significantly higher in the former group. Conclusions: Our study demonstrated that disease presentation severity of African-Latin American cSLE patients is comparable with Caucasian. Mucocutaneous manifestations and autoantibodies profile were the only distinctive features of the former group. The unique mixed background of Brazilian patients probably minimized race diversity spectrum of these patients.Key Points• Our study demonstrated that disease presentation severity of African-Latin American cSLE patients is comparable with Caucasian.• Mucocutaneous manifestations and autoantibodies profile were the only distinctive features of African-Latin American cSLE patients.• African-Latin American cSLE patients had more often anti-phospholipid antibodies and hypocomplementemia.• The unique mixed background of Brazilian patients probably minimized race diversity spectrum of these patients.
Keywords: Anti-phospholipid antibody; Childhood-onset systemic lupus erythematosus; Ethnicity; Race